Chemistry Learning Innovation: Discovery Learning Modified STAD to Motivate and Complete Learning of Inclusive Classroom Students - Tyas, Bella Wahyuning; Agatha, Berliana; Selviana, Elfa; Tikandi, Maulida Iftina Belladona; Azizah, Putri Nur; Gholiyah, Sanih; Yonata, Bertha; Aini, Khurrotul (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to find out the impact of Discovery Learning model combined with Student Teams Achievement Division (STAD) method on students' learning motivation in the one of inclusion class at SMAN 10 Surabaya. This study used a Collaborative Classroom Action Research (CCAR) approach with the Kurt Lewin model. This model contain of four stages, among them are: plan, action, observation, and reflection. The subjects on this research were 36 learners, including 4 learners with special needs. The results be seen that in cycle I, the implementation of Discovery Learning had not fully increased students' learning motivation. However, after improvements were made in cycle II by integrating the STAD method, there was a very significant improvement in motivation indicators, especially in the aspect of tenacity in facing difficulties. The mode score of learning motivation increased from 2 to 3 on this indicator, indicating a high learning motivation category. In addition, cognitive learning outcomes also improved, with 69.4% of students achieving learning completeness according to school criteria. Therefore, in summary that the Discovery Learning strategy combined with the Student Teams Achievement Division (STAD) method is effective to improve the motivation and learning outcomes of inclusion class students.